The Relationship Between Southeast Nigerian Students' Interest in Economics and the Methods Used by Economics Teachers to Teach It - Uda, Kalu Chidinma; O, Oleabhiele Eric; Wokji, Gotip Nehemiah (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This study evaluated how South East Nigerian students' interest in economics correlated with the teaching methods of economics teachers. Descriptive statistics of the correlational type were used in the research methodology; the sample size for the study was chosen using purposive and proportionate sampling techniques; the mean and standard deviation were used to answer the research questions; Pearson product-moment correlation and the one-way ANOVA F-test were used to test the hypotheses. The study's conclusions demonstrated a strong correlation between students' academic interest in economics and the methods used by economics teachers to teach the subject. The study made several recommendations. Based on its findings, educational administrators should designate professionally educated economists with a foundation in economic pedagogies to teach economics; delivering teaching effectively will result from this. Teachers of economics should make an effort to motivate students to study and to introduce the subject using any suitable teaching strategies. In addition, educating and retraining economics instructors inefficient teaching methods for the classroom.